Rippling : - Schwartz, Beverly (Jossey-Bass, 2012)
Rippling reveals proven principles that drive significant change and draws on Beverly Schwartz's vast knowledge and experience of working with hundreds of the world's top social change leaders. Schwartz is vice president at Ashoka, the global organization that works to ensure that social entrepreneurs and their innovations inspire a generation of changemakers to help sustain and support large scale social change.